Pengaruh Diglossia terhadap Pendidikan: Peran Diglosia terhadap Keberhasilan Pembelajaran Bahasa Indonesia sebagai Bahasa Kedua pada Jenjang Sekolah Dasar - Huda, Aninda Nurfazriyatul; Az-Zahra, Meri; Rachman, Ichsan Fauzi (UPA Bahasa Universitas Tidar And HISKI Kedu, 2024)
This research is motivated by questions regarding the role of diglosia in the success of learning Indonesian as a second language in elementary schools. This research aims to reveal the role of diglosia in second language learning and its impact on the first language using a qualitative approach. The type of research used is descriptive analysis. The data collection technique is literature study, namely by collecting library data, reading and taking notes, as well as processing research materials. The research subjects are various sources of library information. The results of the research are based on analysis of the data obtained, namely that diglosia has a role in selecting learning methods and determining the success of learning Indonesian as a second language. This can be seen from the process of using Indonesian as a second language in the school environment which is influenced by the use of the first language in the family environment. and the use of the T variety and R variety in Indonesian in formal and informal situations at school.